Catalyst‐Substrate Effects on Biocompatible SABRE Hyperpolarization1. Issue 2 (27th November 2018) - Manoharan, Anand; Rayner, Peter J.; Fekete, Marianna; Iali, Wissam; Norcott, Philip; Hugh Perry, V.; Duckett, Simon B.
Abstract: The hyperpolarization technique, Signal Amplification by Reversible Exchange (SABRE), has the potential to improve clinical diagnosis by making molecular magnetic resonance imaging in vivo a reality. Essential to this goal is the ability to produce a biocompatible bolus for administration. We seek here to determine how the identity of the catalyst and substrate affects the cytotoxicity by in vitro study, in addition to reporting how the use of biocompatible solvent mixtures influence the polarization transfer efficiency. By illustrating this across five catalysts and 8 substrates, we are able to identify routes to produce a bolus with minimal cytotoxic effects. Abstract : Routes to ensure the biocompatibility of a hyperpolarized agent delivered by signal amplification by reversible exchange are assessed for cytotoxicity. While substrates can improve cell survival, the identity of the catalysts′ iridium‐carbene ligand does not have an impact. Residual iridium content is found to be the largest contributor to cell death and should therefore be minimized prior to in vivo administration.